Case report: Successful treatment of hyperkalemia during general anesthesia in a domestic cat - Irizarry, Tiffany; Gradilla, Sarah (Frontiers in Veterinary Science, 2024)
Objective This study aimed to describe the successful identification and treatment of severe hyperkalemia, cardiac arrhythmia, rhabdomyolysis, and acute kidney injury (AKI) in a domestic cat that underwent general anesthesia for abdominal exploratory surgery. The definitive underlying cause remains unknown; however, a reaction to propofol is suspected. Case summary A 6-month-old intact male domestic short-hair cat underwent general anesthesia and developed severe intraoperative rhabdomyolysis, hyperkalemia, ventricular fibrillation, and AKI during surgery despite a documented mild hypokalemia and normal creatinine before inducing anesthesia. Propofol was administered as part of the anesthetic protocol. The patient was resuscitated successfully and responded well to advanced medical intervention. The hyperkalemia and AKI were resolved within less than 24 h from surgery and rhabdomyolysis was resolved at the time of recheck 5 days later. New or unique information provided While previously suspected in dogs, to the authors’ knowledge, propofol-related infusion syndrome (PRIS) has not been reported in domestic cats. Veterinary professionals should be aware that drug-induced intraoperative rhabdomyolysis and hyperkalemia can develop unexpectedly and should remain a differential for acute cardiac arrhythmias or cardiac arrest and AKI.